Core - shell particle reinforcements - a new trend in the design and development of metal matrix composites - Dudina, Dina V.; Georgarakis, Konstantinos (MDPI, 2022)
Metal matrix composites (MMCs) are a constantly developing class of materials. Simultaneously achieving a high strength and a high ductility is a challenging task in the design of MMCs. This article aims to highlight a recent trend: the development of MMCs reinforced with particles of core–shell structure. The core–shell particles can be synthesized in situ upon a partial transformation of metal (alloy) particles introduced into a metal matrix. MMCs containing core–shell particles with cores of different compositions (metallic, intermetallic, glassy alloy, high-entropy alloy, metal-ceramic) are currently studied. For metal core–intermetallic shell particle-reinforced composites, the property gain by the core–shell approach is strengthening achieved without a loss in ductility. The propagation of cracks formed in the brittle intermetallic shell is hindered by both the metal matrix and the metal core, which constitutes a key advantage of the metal core–intermetallic shell particles over monolithic particles of intermetallic compounds for reinforcing purposes. The challenges of making a direct comparison between the core–shell particle-reinforced MMCs and MMCs of other microstructures and future research directions are discussed.
Keywords: core–shell particle; reinforcement; metal matrix composite; interface